Acute Myocardial Infarction : A Study Of Door-To-Needle Time Of Thrombolytic Therapy - Osman, Sharifudin (2001)
The objectives of this study were firstly to show that it is possible to start throlnbolytic therapy for acute Inyocardial infarction in the Elnergellcy Depart1nent, Hospital Kuala Lumpur and probably in other emergency departments of other hospitals in the cOlmtry. Secondly to show that the door to needle tilne is shorter if we were to start the thrombolytic therapy in the emergency department rather than in the coronary care lullt ward. Thirdly that there would be an improvement in the door to needle time in the management of acute tnyocardial infarct in the elnergency departInent once the staff of the departtnent had Inore experience.